A Retrospective, Observational Study of Catheter-Associated Urinary Tract Infection Events Post-Implementation of a Novel Urinary Catheter System with Active Drain Line Clearance and Automated Intra-Abdominal Pressure Monitoring - Patrick Brockway; David M. Hill; Vanessa Moll; Kelly Stanton; Manu L. N. G. Malbrain; Sai R. Velamuri (Life, 2022)
Objective: A quality improvement study to assess catheter-associated urinary tract infection (CAUTI) rate post-implementation of a bladder catheter with integrated active drain line urine clearance and automated intra-abdominal pressure monitoring in a burn intensive care unit (ICU). DESIGN: Eight-year retrospective before and after study (2015–2022). Setting: A single American Burn Association-verified Burn Center with 14 inpatient beds. Patients: Patients meeting criteria for admission to a Burn Center. Methods: Retrospective cohort study following the implementation of a novel urine output monitoring system with integrated drain line and urine clearance. Data from a 48-month (from January 2015–December 2018) historical control (period 1) were compared to data from a 28-month (from January 2020 to April 2022) post-implementation period (period 2). Pre- and post-implementation CAUTI event incidences were compared. Patients were transferred from outside hospitals with gravity bladder. A distinction in the chart between catheter types was impossible. Charts were reviewed to characterize patients with CAUTI events. Results: A total of 42 CAUTIs in 2243 patients were identified using the National Health and Safety Network (NHSN) definition during the analyzed period. There were 40 CAUTI events in period 1 and two CAUTIs in period 2. The incidence of CAUTI events pre-implementation was 0.030 (mean of 10 CAUTI events per year) compared to 0.002 (mean of 1 CAUTI event per year) post-implementation of an automatic drain line clearing UO monitoring system showing a significant reduction in CAUTI events (p < 0.01, risk ratio novel vs. gravity bladder catheter 0.071, 95% confidence interval: 0.017–0.294). Conclusions: CAUTIs were reduced in the period following the implementation of a novel urinary catheter system with an integrated active drain line and urine clearance in burn patients.